The intestinal microbiome of the pig - Isaacson, Richard; Kim, Hyeun Bum (Animal health research reviews, 2012)
The intestinal microbiome has been the subject of study for many decades because of its importance in the health and well being of animals. The bacterial components of the intestinal microbiome have closely evolved as animals have and in so doing contribute to the overall development and metabolic needs of the animal. The microbiome of the pig has been the subject of many investigations using culture-dependent methods and more recently using culture-independent techniques. A review of the literature is consistent with many of the ecologic principles put forth by Rene Dubos. Animals develop an intestinal microbiome over time and space. During the growth and development of the pig, the microbiome changes in composition in a process known as the microbial succession. There are clear and distinct differences in the composition of the pig intestinal microbiome moving from the proximal end of the intestinal tract to the distal end. The majority (>90%) of the bacteria in the pig intestinal microbiome are from two Phyla: Firmicutes and Bacteroidetes. However, the ileum has a high percentage of bacteria in the phylum Proteobacterium (up to 40%). Perturbations to the microbiome occur in response to many factors including stresses, treatment with antibiotics, and diet.